Numerical Simulation of a Two-Dimensional Vertically Averaged Groundwater Quality Assessment in Homogeneous Aquifer Using Explicit Finite Difference Techniques - Supawan Yena; Nopparat Pochai (My University, 2020)
Leachate contamination in a landfill causes of pollution that flowing down to the groundwater.There are many methods to measure the groundwater quality.Mathematical models are often used to describe the groundwater flow.In this research, the affection of landfill construction to groundwater-quality around rural area are focused.Three mathematical models are combined.The first model is a two-dimensional groundwater flow model.It provides the hydraulic head of the groundwater.The second model is the velocity potential model.It provides the groundwater flow velocity.The third model is a two-dimensional vertically averaged groundwater pollution dispersion model.The groundwater pollutant concentration is provided.The forward time centered technique with the centered in space, the forward in space and the backward in space with all boundaries are used to obtain approximate hydraulic head, the flow velocity in x-and y-directions, respectively.The approximated groundwater flow velocity is used to input into a two-dimensional vertically averaged groundwater pollution dispersion model.The forward time centered space technique with the centered in space, the forward in space and the backward in space with all boundaries are used to obtain approximate the groundwater pollutant concentration.The proposed explicit forward time centered spaced finite difference techniques to the groundwater flow model the velocity potential model and the groundwater pollution dispersion model give good agreement approximated solutions.
Keywords: Groundwater model; Groundwater flow equation; Hydraulic head; Groundwater Pollution; Numerical methods in engineering